ANALYSIS OF THE VOLUME OF AGRICULTURAL AND AVIATION WORKS IN UKRAINE - Mnatskanov, R.; Pron, S.; Lahutochkin, V. (Science-based technologies, 2013)
The agricultural sector of Ukraine is significantly changing with implementation of innovative technologies in growing crops. The same tendency is characteristic of plant growing, and, as a result, the correlation of the volumes of different works, in particular, the agricultural and aviation works shifts greatly. The following article presents analysis and defines the current volume of different types of agricultural and aviation works and suggests the overall seasonality trend for all types of agricultural and aviation works. In addition, the article provides analysis of the total volume of agricultural and aviation works in Ukraine over the period 2011-2013. The statistical data on the dynamics of agricultural and aviation works are reviewed, such as: pest and weed control, control of plant diseases, fertilizer dressing, defoliation and crop desiccation. The general trend in seasonality of agricultural and aviation works is defined.